Self-motivation, family support, and hemodialysis adherence among patients with chronic kidney disease - Iskim Luthfa; Abrori Abrori; Yunancik Zaenal Siswanto (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Maintenance hemodialysis requires sustained adherence to treatment schedules, medication, dietary recommendations, and fluid restrictions. Adherence may be influenced by patients' internal motivation and the support available within the family. Purpose: To examine the associations of self-motivation and family support with hemodialysis therapy adherence among patients with chronic kidney disease. Method: This cross-sectional study included 143 patients receiving maintenance hemodialysis at two hospitals in Tangerang, Indonesia. Participants were recruited through total sampling from September to November 2025. Self-motivation, family support, and treatment adherence were assessed using structured questionnaires. Associations were analyzed using Spearman's rank correlation test. Results: Low self-motivation was the largest category, reported by 53 participants (37.1%), and low family support was reported by 51 participants (35.7%). Regarding adherence, 53 participants (37.1%) were partially adherent and 48 (33.6%) were non-adherent. Self-motivation (ρ = 0.611, p < 0.001) and family support (ρ = 0.607, p < 0.001) each showed a strong positive correlation with hemodialysis adherence. Conclusion: Higher self-motivation and stronger family support were associated with greater adherence to hemodialysis therapy. Nursing strategies that strengthen patient engagement and involve family members may support adherence to long-term treatment.